Even though I normally don't do it, I'm going to denote the derivative of a function as "prime" by adding an apostrophe at the end. That would mean
(sinx)' = cosx
(x^5)' = 5x^4
The way the chain rule works is that you would solve the derivative normally as if it were x, and then take the derivative of the inside. Therefore
(sin[junk])' = (cos[junk]) ([junk]')
([junk]^5)' = (5[junk]^4) ([junk]')
This is no different. If f(x) = (x^2 + x)^2, then
f'(x) = 2(x^2 + x) * (x^2 + x)'
f'(x) = 2(x^2 + x) (2x + 1)
2006-12-27 17:07:22
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Using the chain rule, you can get the derivative = 2(x^2+x)(2x+1).
2006-12-28 00:45:04
·
answer #2
·
answered by sahsjing 7
·
0⤊
0⤋
First derivative is 2(x^2 + x)(2x + 1) by the chain rule
This can be simplified to 2x(x +1)(2x + 1)
2006-12-28 00:43:55
·
answer #3
·
answered by A S 4
·
0⤊
0⤋
The product is x^4 + 2x^3 + x^2,
and its derivative is therefore 4x^3 + 6x^2 + 2x.
2006-12-28 01:33:56
·
answer #4
·
answered by Asking&Receiving 3
·
1⤊
0⤋
Using the Chain Rule, which states that if if y=f(u) and u=g(x) then the derivative of f(u) would be
d/dx f(u)= f'(u) x g'(x)
so!
d/dx (x^2 + x)^2 = 2(x^2 + x) multiplied by (2x + 1)
=2x^2 + 2x (2x + 1)
= 4x^3 + 2x^2 + 4x^2 + 2x
= 4x^3 + 6x^2 + 2x
hope it helped =)
2006-12-28 00:49:11
·
answer #5
·
answered by principessa=o) 2
·
0⤊
0⤋
(x^2 + x)^2
(x^2 + x)(x^2 + x)
x^4 + x^3 + x^3 + x^2
x^4 + 2x^3 + x^2
4x^3 + 6x^2 + 2x
2006-12-28 12:14:51
·
answer #6
·
answered by Sherman81 6
·
2⤊
0⤋
Go to http://www.math.com
2006-12-28 01:35:27
·
answer #7
·
answered by Prem P 2
·
0⤊
0⤋